The Effect of Job Insecurity on Turnover Intention with Organizational Commitment as an Intervening Variable at PT Singgalang Beton Perkasa, Padang Pariaman Regency - Wijaya, Hafis Maulana; Trinanda, Okki (Human Resource Management Studies, 2023)
The purpose of the study is to analyze the effect of job insecurity, organizational commitment to employee turnover intention, the effect of job insecurity on organizational commitment and organizational commitment mediating positively and significantly on the relationship between job insecurity and turnover intention at PT. Singgalang Beton Perkasa Fogpaten Padang Pariaman. Causal associative research methods with quantitative techniques. The population of all employees is 52 employees with a sample of 52 respondents. Data collection using questionnaires. The data analysis techniques used in this study are descriptive and quantitative analysis. Hypothesis testing uses multiple linear regression tests. Based on the research findings, it is known that: (1) Job insecurity has a positive and significant influence on turnover intention at PT. Singgalang Beton Perkasa, Padang Pariaman Regency, with a magnitude of 0.326 or 32.6% with a significance level of 0.010. (2) Organizational commitment has a positive and significant influence on turnover intention at PT. Singgalang Beton Perkasa, Padang Pariaman Regency. This is evident from the partial hypothesis test result of 0.406 or 40.6% with a significance level of 0.002. (3) Job insecurity has a positive and significant influence on organizational commitment among employees of PT. Singgalang Beton Perkasa in Padang Pariaman Regency, with a magnitude of 0.343 or 34.3% with a significance level of 0.013. (4) Organizational commitment mediates the relationship between job insecurity and turnover intention at PT. Singgalang Beton Perkasa, Padang Pariaman Regency, with a positive and significant effect of 0.489 or 48.9% with a significance level of 0.000..